Cost-effectiveness analysis of Shexiang Baoxin Pill (MUSKARDIA) as the add-on treatment to standard therapy for stable coronary artery disease in China. - Jie Pan; Ping-da Ping; Wei Wang; Jia-Meng Zhou; Wen-Tao Zhu (PLoS ONE, 2024)
Background Recent evidence indicates that Shexiang Baoxin Pill (MUSKARDIA), as an add-on treatment to standard therapy for stable coronary artery disease (CAD), is effective. Nevertheless, the cost-effectiveness of introducing the Shexiang Baoxin Pill (Abbreviation SBP) to the current standard treatment for patients with CAD in China remains unknown. Objective The objective of this study was to assess the cost-effectiveness of introducing SBP into the current standard treatment in China for patients with CAD. Method The effects of two treatment strategies-the SBP group (SBP combined with standard therapy) and the standard therapy group (placebo combined with standard therapy)-were simulated using a long-term Markov model. The simulation subjects might experience non-fatal MI and/or stroke or vascular or non-vascular death events. The study parameters were primarily derived from the MUSKARDIA trial, which was a multicenter, double-blind, placebo-controlled phase IV randomized clinical trial. Furthermore, age-related change, event costs, and event utilities were drawn from publicly available sources. Both costs and health outcomes were discounted at 5.0% per annum. One-way and probabilistic sensitivity analyses were conducted to verify the robustness of the model. Based on the MUSKARDIA trial results, the risk with the events of major adverse cardiovascular events (MACE) was decreased (P < 0.05) in the female subgroup treated with SBP therapy compared with standard therapy. Consequently, a scenario analysis based on subgroups of Chinese females was conducted for this study. Incremental cost-effectiveness ratios (ICERs) were assessed for each strategy for costs per quality-adjusted life-year (QALY) saved. Results After 30 years of simulation, the SBP group has added 0.32 QALYs, and the cost has been saved 841.00 CNY. Compared with the standard therapy, the ICER for the SBP therapy was -2628.13 CNY per QALY. Scenario analyses of Chinese females showed that, after 30 years of simulation, the SBP therapy has been increased by 0.82 QALYs, and the cost has been reduced by 19474.00 CNY. Compared with the standard therapy, the ICER for the SBP therapy was -26569.51 CNY per QALY. Similar results were obtained in various extensive sensitivity analyses. Conclusions This is the first study to evaluate the cost-effectiveness of SBP in the treatment of CAD. In conclusion, SBP as an add-on treatment to standard therapy appears to be a cost-effective strategy for CAD in Chinese patients.